Renal papillary hypertrophy, a rare mimicker of upper tract urothelial carcinoma: A case report - Navid Ahamdi; Seyed Mohammad Kazem Aghamir (SAGE Open Medical Case Reports, 2022)
Renal papillary hypertrophy is a rare variation that mimics upper tract urothelial carcinoma. This is the ninth case in literature. It causes hematuria and pain, or it could be asymptomatic. It is important to distinguish this variation from malignant masses since misdiagnosis leads to unnecessary radical surgery. Flexible ureteroscopy helps distinguish malignant from benign masses, particularly in cases where there is not a consensus on the exact pathology of the mass. We present a 46-year-old female who came with hematuria and was planned to undergo radical nephroureterectomy under the impression of renal cell carcinoma based on imaging studies. After flexible ureteroscopy, renal papillary hypertrophy was confirmed and radical nephroureterectomy was prevented.